Financial inclusion acceleration research: analysis of fintech adoption enggagement in generation Z - Intan Prastiwi, Putri; Chotidjah Suhatmi, Erna; Mutma’ina, Evi (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
Financial Technology (Fintech) as a form of digitalization of the rapid development of technology used in the banking sector. The increasing number of fintech users on banking and non-banking platforms is due to the facilities offered by fintech in the form of digital banks and e-wallets in the form of crowdfunding facilities, microfinancing, p2p lending services, market aggregators, digital payment systems. These various services provide convenience for their users. The condition of Indonesian society which is dominated by production groups called the millennial generation and generation Z aims to strengthen the opportunities and challenges of digital transformation. The focus of this study discusses the factors for the adoption of fintech banking or non-banking in generation Z. The research method uses a qualitative method through interviews with respondents. The sampling method uses the snowball method. The results of the study show that the factors for the adoption of financial technology in generation Z are lifestyle, hedonic behavior, social influence.